The Edifying Role of Portuguese and Castilian Synods (14th and 15th centuries) - Teodoro, Leandro Alves [UNESP] (Univ Coimbra, Fac Letras, 2024)
In the mid-14th century, the bishops of Portugal and Castile took on with greater fervor the duty of guiding the souls of faithful Christians so that they could instruct themselves and purge their sins. Focusing on synodal constitutions -the set of rules and advice read by the prelates at synods- this text aims to analyze to what extent the preachings of these ecclesiastical authorities of Portugal and Castile employed similar proposals to guide men and women in these Catholic realms in knowing how to profess the Christian religion. In other words, this study seeks to emphasize the similarities between the moralizing proposals of prelates from various regions of these kingdoms, which were carried out between the mid-14th and the late 15th centuries, a period of consolidation in Iberian lands of the ecclesiastical reform initiated in the times of the Fourth Lateran Council (1215).
Keywords: Synods; Portugal; Castile; edification; 14th and 15th centuries